The plague of the Sahel - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1993)
Grasshoppers and locusts: the plague of the Sahel by John Rowley and Olivia Bennett 1993 64pp ISBN 1 870670 24 8 Pbk price UKL7.95 Panos Publications Ltd 9 White Lion Street London N1 9PD UK